ANTIBACTERIAL EFFECTIVENESS OF LERAK FRUIT ETHANOL EXTRACT (Sapindus rarak DC) AND 2% CHLORHEXIDINE IN Enterococcus faecalis - Hartanto Endrowahyudi; Irfan Fathon; Rudi Satria Darwis; Ratih Widyasari (Fakultas Kedokteran Gigi Unjani, 2021)
The failure of a root canal treatment can be caused by the facultative anaerobic bacteria Enterococcus faecalis, which should be eliminated throughout root canal irrigation. Chlorhexidine 2% is a popular antibacterial liquid used in root canal irrigation. Natural substances can also be used to make antibacterial irrigation liquids. One natural substance with antibacterial properties is lerak fruit extract (Sapindus rarak DC), containing 28 per cent of saponins, alkaloid compounds, polyphenols, antioxidant chemicals, and flavonoid groups and tannins. This study was conducted to determine the effectiveness of 25% lerak fruit extract (Sapindus rarak DC) against E. faecalis compared to 2% Chlorhexidine. This study is a pure experimental study using the agar diffusion method against three experimental groups chlorhexidine 2% as a positive control, lerak fruit extract (Sapindus rarak DC) as a treatment group, and aquadest as a negative control. Each group was repeated ten times on Muller Hinton Agar (MHA) media which was applied using a paper disc. Then the diameter of the inhibition zone was calculated using a caliper. The results in this study, 25% lerak (Sapindus rarak DC) fruit extract had an average inhibition zone diameter of 11.775 mm, and an average inhibition zone diameter of 2% chlorhexidine was 19.745 mm. The difference in the diameter of the inhibition zone was significantly different in all groups. Conclusion ethanol extract of lerak fruit (Sapindus rarak DC) 25% can inhibit the growth of E. faecalis and can be used as an alternative to other antimicrobial agents as disinfection of root canal irrigation. DOI : 10.54052/jhds.v1n2.p188-196